2015
DOI: 10.14444/2063
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Prediction in a Vertebral Compression Fracture Population: the ASA Physical Status Score versus the Charlson Comorbidity Index

Abstract: Background Morbidity and mortality scores are useful to control for medical comorbidities in study populations where either effects of an illness or benefits of a treatment are examined. Our study examined if a direct relationship existed between the American Society of Anesthesiologists Physical Status (ASA) score and the Charlson Comorbidity Index (CCI) in an osteoporosis population where patients had sustained a vertebral compression fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 17 publications
1
22
1
Order By: Relevance
“…17 Correlations between ASA scores and postoperative morbidity and mortality are often inconclusive. [17][18][19][20][21][22][23] While several studies demonstrated a close relation to the ASA score and morbidity, mortality, operating times, length of hospitalization, postoperative complications, health care costs, and different other variables, 17,18,[20][21][22][23] other studies were not able to confirm these findings. 19 In an era of fixed fees and rising economic pressure in worldwide health care systems, it becomes increasingly important to establish well-supported indications to perform complex surgeries, such as microsurgical free flap reconstructions.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…17 Correlations between ASA scores and postoperative morbidity and mortality are often inconclusive. [17][18][19][20][21][22][23] While several studies demonstrated a close relation to the ASA score and morbidity, mortality, operating times, length of hospitalization, postoperative complications, health care costs, and different other variables, 17,18,[20][21][22][23] other studies were not able to confirm these findings. 19 In an era of fixed fees and rising economic pressure in worldwide health care systems, it becomes increasingly important to establish well-supported indications to perform complex surgeries, such as microsurgical free flap reconstructions.…”
mentioning
confidence: 96%
“…3,4,[9][10][11][12][13][14][15] However, while well established in other surgical specialties, few studies have solely focused on the potential effect of the preoperative medical state of the patients as one possible factor influencing the outcome of free flap reconstructions. 16 The preoperative medical status is normally assessed and classified according to the American Society of Anesthesiologists (ASA) score of physical status 11,17,18 which was introduced by Rovenstein, Saklad, and Taylor in 1941 as a grading system for the surgical patients' preoperative health. 17 In 1963, the ASA score was modified to its current form.…”
mentioning
confidence: 99%
“…We did not find such a difference, even in the high-risk subgroup or in the group of patients with THA in the course of a hip fracture. However, we adjusted for comorbidity by ASA class, whereas Garland et al adjusted by modified Charlson Comorbidity Index, which may have slightly different effect (Lavelle et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, ASA score was used for the assessment of comorbidity instead of the Charlson comorbidity index, in order to evaluate the functional impact of other diseases than the index cancer. The ASA score is widely used to describe preoperative physical status, but also to describe comorbidity [23,24]. A recently published study has shown agreement between the ASA score and Charlson comorbidity index score [23] indicating that both systems are applicable for the assessment of comorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…The ASA score is widely used to describe preoperative physical status, but also to describe comorbidity [23,24]. A recently published study has shown agreement between the ASA score and Charlson comorbidity index score [23] indicating that both systems are applicable for the assessment of comorbidity. Due to the limited number of patients, comparison of survival based on the different treatment regimens was not possible.…”
Section: Discussionmentioning
confidence: 99%